PEMBERDAYAAN GURU ANAK-ANAK PEKERJA MIGRAN INDONESIA DI SANGGAR BIMBINGAN (SB) MALAYSIA MELALUI PELATIHAN MEDIA SEPER - Yulia Maftuhah Hidayati (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The purpose of this service activity is to empower teachers from the children of Indonesian Migrant Workers through smart board-based SEPER media at the Malaysian Guidance Studio. Studio teachers, feel the needget extraknowledge and skills in teaching so that the quality of education for children in Malaysia is not neglected. This training consists of several stages, namely (1) The Preparation Stage includes both internal and external coordination regarding the implementation of activities, manufacturer instrument such powerpoint, teacher attendance, documentation, time allocation (2) The implementation stage which includes the opening of the training program, presentation of material, question and answer discussion and closing. The methods used are lecture, demonstration, and question and answer methods. To measure the success of this community service activity, an evaluation is carried out by means of question and answer. This service activity is carried out directly and through Google Meeting. From the results of the question and answer session, it was found that teachers who participated in the training could understand the importance of using instructional media, especially in mathematics. Teachers who participated in the training understood and agreed that Smartboard-Based SEPER Media could increase students' enthusiasm for learning so that they could achieve learning objectives and improve student learning outcomes so that Malaysian SB students who were children of Indonesian Migrant Workers could improve their quality. This service went quite smoothly and efficiently even though there were a few network problems for teachers who took part in online training. Teachers at the Guidance Studio who participated in the training were very enthusiastic in welcoming this service, as evidenced by the many positive responses given. They also want such activities to be sustainable.